TECHNOLOGICAL EQUIPMENT FOR PLASTIC FORMING OF A WIDE FLANGE IN PIPE BLANK - L. A. Isaevich; D. M. Ivanickij; A. M. Sidorenko (Литьë и металлургия, 2015)
Describes the features of the design of technological equipment for plastic forming wide flanges in pipe blanks and accessories for the implementation of the technological process. Shows the dependence for determining deforming efforts. Scheme of the stamp to simulate the process of flanging and local deformation of the toroidal section in the flange are presented.